Pointing Acquisition and Tracking System for Free Space Optical Communication Based on Integrated Optical Phased Array - Lei Chen; Lei Zhu; Heng Du; Xiangyu Wang; Shiyang Shen; Yihao Wang; Shan Zhao; Xiaodong Wang (IEEE Photonics Journal, 2025)
With proliferation of low-earth-orbit satellite (LEOs) constellations, air-to-space laser communications have the potential to realize aircraft broadband Internet services due to its high speed and low latency. A major challenge in aircraft to LEOs laser link is the fast scanning, high-bandwidth pointing acquisition tracking (PAT) approach to achieve rapid link establishment and handover as well as to compensate for errors caused by vibrations of the aircraft platform. In this paper, a PAT system based on integrated optical phased array (OPA) and four quadrant detector (QD) is demonstrated. Rapid azimuth beam scanning is achieved by controlling the OPA’s 512 thermal phase shifters, while elevation scanning is carried out by adjusting the laser’s wavelength. The arrival angle of the incident beacon is measured by QD and used to adjust the emission direction through FPGA. The experiment shows that the beam steering rise time is less than 60 μs in azimuth and 46 μs in elevation, while the pointing accuracy is <0.05° (RMSE) within the field of 5° × 5°. The calculated closed-loop bandwidth is >2.5 kHz. The PAT system has low complexity, small size, mechanical-free beam agility steering, and high tracking bandwidth capability.